2018
DOI: 10.1098/rsos.180172
|View full text |Cite
|
Sign up to set email alerts
|

Walking together: behavioural signatures of psychological crowds

Abstract: Research in crowd psychology has demonstrated key differences between the behaviour of physical crowds where members are in the same place at the same time, and the collective behaviour of psychological crowds where the entire crowd perceive themselves to be part of the same group through a shared social identity. As yet, no research has investigated the behavioural effects that a shared social identity has on crowd movement at a pedestrian level. To investigate the direction and extent to which social identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 47 publications
1
55
0
Order By: Relevance
“…Most often, pushing forward is named as a strategy (131), followed by filling gaps (57), choosing the right or left side or middle as the preferred pathway (46) and standing at the front at the beginning (37). The following reasons for not being able to influence the entrance procedure were given: no room for manoeuvre (100), an initial position at the back (30), being too weak (16), consideration for others (9).…”
Section: What Strategies Did You Use For Accessing Faster/why Could Ymentioning
confidence: 99%
“…Most often, pushing forward is named as a strategy (131), followed by filling gaps (57), choosing the right or left side or middle as the preferred pathway (46) and standing at the front at the beginning (37). The following reasons for not being able to influence the entrance procedure were given: no room for manoeuvre (100), an initial position at the back (30), being too weak (16), consideration for others (9).…”
Section: What Strategies Did You Use For Accessing Faster/why Could Ymentioning
confidence: 99%
“…Although this was outside our scope of investigation, it is important to note the existence of a research stream that also investigates the occurrence of such effects, under the perspective of social identity theory (e.g., Drury & Reicher, , , ; Hopkins et al, ; Reicher, ; Templeton, Drury, & Philippides, ). This stream is well established and has provided major contributions to the study of collective gatherings.…”
Section: Perspectivesmentioning
confidence: 99%
“…theory (e.g., Drury & Reicher, 1999, 2005, 2009Hopkins et al, 2016;Reicher, 2017;Templeton, Drury, & Philippides, 2018). This stream is well established and has provided major contributions to the study of collective gatherings.…”
Section: Per S Pec Tive Smentioning
confidence: 99%
“…Crucially, they do not include macro-level social influences on behaviour and so neglect the role of connections between pedestrians on movement. For example, previous research from crowd psychology [17] demonstrated that a crowd of pedestrians reduced their walking speed and increased their distance walked to remain in close proximity to one another when they perceived one another to be fellow group members. Thus, rather than manoeuvring around one another to reach a target, the group members manoeuvred around one another to remain together on the basis of shared group membership.…”
Section: Approaches To Pedestrian Behaviourmentioning
confidence: 99%
“…Crucially, shared social identification affects the proximity of pedestrians to one another. Templeton, Drury, and Philippides [17] demonstrated that pedestrians in a crowd who were primed to share a social identity (i.e., a psychological crowd) walked in closer proximity to one another, further, and slower, than when they had not been primed (i.e. were simply part of a physical crowd).…”
Section: Incorporating Inter-and Intragroup Psychologymentioning
confidence: 99%